Principles of cattle production - Phillips, C. J. C. (CABI, 2009)
This edition presents a vision for a new cattle industry: an industry that will contribute to the environment, to the welfare of cattle and to the provision of high-quality food for an increasingly demanding world population. The book covers the principles of cattle reproduction, describing the latest techniques for breed improvement as well as the reproductive technologies that can be used to achieve these improvements. The merits of the different breeds for dairy and beef production are discussed. Oestrous behaviour in the cow is given special consideration in view of its importance to reproductive management. As well as describing the latest methods of cattle farming, the book pays particular attention to the impact of cattle farming on the environment. In the light of this, the future roles for cattle are considered in relation to the needs of both developed and developing regions of the world. The evolution of cattle production systems in different parts of the world is also described to place this in context. It is hoped that the book will be useful for all those involved in the cattle farming industry, enabling them to develop systems that meet modern requirements for safe food, produced in accordance with the animals' welfare requirements and with minimal or no adverse impact on the environment.